The Horizontal Alignment Design for Jalan Munjul – Sindang Resmi, Pandeglang - Banten - Erwin Batista; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2023)
The improvement of road infrastructure plays an important role in ensuring the prosperity of nations all over the world. Indonesia is also taking part in the development of road infrastructure in each region. In the province of Banten, Pandeglang Regency has some of its finest natural and economic potentials. To encourage economic connectivity to the surrounding districts, the development of this potential must be supported by appropriate infrastructure development. Planning a connecting road for the Munjul Sindangresmi could be a way to shorten the flow of traffic in the Munjul sub-district. The route was planned manually using the AutoCAD(R) 2D application, Google Earth Pro, Global Mapper, and other supporting applications. Planning begins with determining the road alignment plan, which is then projected on the plan location map. Then, apply the topographic map observations from remote imagery mapping. After that, continue with the road geometry design calculation depending on the location of the chosen route. The requirements that must be followed while determining the road geometry—which in this case is a horizontal alignment—refer to the Road Geometry Design Guidelines that were published by the Directorate General of Highways in 2021. The road geometry planning results in this journal have a length of 2.3 Km with a horizontal alignment design consisting of 3 horizontal curves, 2 Spiral - Circle - Spiral (SCS) curves, and 1 Full Circle arc. To assess the value of the economic and safety benefits of this road design, future planning for this road should consider the amount of embankment excavations as well as a project feasibility study.